THE RELATIONSHIP BETWEEN THE HEALTH BELIEF MODEL AND DRUG INFORMATION SERVICES PROVIDED BY PHARMACISTS TO PREGNANT AND BREASTFEEDING WOMEN - Septi Anggraini; Elida Zairina; Wahyu Utami (The Indonesian Journal of Public Health, 2021)
ABSTRACTThe use of medication during pregnancy and breastfeeding cannot be avoided, particularly for those with chronic diseases. The use of medication for these patients require special attention, especially by pharmacists as they have the responsibility to provide medications and appropriate services to achieve optimal therapeutic goals. The drug information service actively provided by pharmacists is a display of their commitment in preventing drug therapy problems and improving the quality of life of pregnant and breastfeeding women. This study aimed to analyze the relationship between pharmacists' beliefs based on the Health Belief Model (HBM) approach and the practice of active drug information service for pregnant and breastfeeding women with chronic diseases. This study was an observational study with a cross-sectional design and used a self-administered questionnaire. 62 pharmacists in Primary Healthcare Centers in Surabaya agreed to participate in this study. The Spearman correlation analysis was used and showed that perceived self-efficacy had the strongest relationship (rs = 0.357) with the practice of providing active drug information. Thus, it can be concluded that perceived self-efficacy is a factor that is directly related to the practice of providing active drug information.Keywords: Active Drug Information Services, Health Belief Model, Pharmacists